The Huncal Member of the Vaca Muerta Formation, Neuquén Basin of Argentina: Insight into biostratigraphy, structure, U-Pb detrital zircon ages and provenance. (June 2020) - Naipauer, Maximiliano; Comerio, Marcos; Lescano, Marina A.; Vennari, Verónica V.; Aguirre-Urreta, Beatriz; Pimentel, Marcio M.; Ramos, Victor A.
Abstract: In the western sector of the Neuquén Basin, the organic-rich shales of the Vaca Muerta Formation are intercalated with turbidite sandstone intervals and slump structures integrated in the Huncal Member. The age of the Huncal sandstones based on the integration of the ammonite faunas, calcareous nannofossils and U-Pb analysis is late Berriasian in their type locality. The origin of this deposit is probably related with two lobes of turbiditic sandstones linked with a progradational regressive phase. Sandstones are lithic arkoses and feldspathic litharenites derived from recycled orogenic and dissected arc sources. The U-Pb ages confirm a mixed sedimentary provenance from the south and southeastern margins of the basin, specifically from Paleozoic and Triassic–Jurassic rocks of the North Patagonian Massif and the Huincul High. The complex fold and fault system described in the sandstone levels was interpreted as the result of slump processes with a main transport direction to the SW and W. Sandstone deposits with slump structures assignable to the Huncal Member are present throughout the entire basin from the Tithonian to the Valanginian in the Vaca Muerta Formation. Therefore, the Huncal Member is a diachronic lithostratigraphic unit and its deposition probably depended on different factors such as relative sea level changes, the position in the ramp system or in the platform and slope configuration and internal morphostructural features of the Neuquén Basin. Highlights: The age of the Huncal sandstones is late Berriasian in their type locality. The sedimentary provenance is from the North Patagonian Massif and the Huincul High. Sandstones and slump structures are present throughout the entire basin from the Tithonian to the Valanginian. The Huncal Member is a diachronic lithostratigraphic unit.